2015
DOI: 10.7554/elife.11859
|View full text |Cite
|
Sign up to set email alerts
|

A G-protein activation cascade from Arl13B to Arl3 and implications for ciliary targeting of lipidated proteins

Abstract: Small G-proteins of the ADP-ribosylation-factor-like (Arl) subfamily have been shown to be crucial to ciliogenesis and cilia maintenance. Active Arl3 is involved in targeting and releasing lipidated cargo proteins from their carriers PDE6δ and UNC119a/b to the cilium. However, the guanine nucleotide exchange factor (GEF) which activates Arl3 is unknown. Here we show that the ciliary G-protein Arl13B mutated in Joubert syndrome is the GEF for Arl3, and its function is conserved in evolution. The GEF activity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
206
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 132 publications
(211 citation statements)
references
References 43 publications
5
206
0
Order By: Relevance
“…Recently, Gotthardt et al (2015) reported that ARL13B serves as a GEF for ARL3, which in turn binds to and stimulates release of PDE6D from C-terminally prenylated proteins, including INPP5E, which are then allowed to enter cilia (Fansa et al, 2016;Ismail et al, 2011). Furthermore, Fansa et al reported that treatment of cells with ARL3 siRNA caused substantial loss of the dominant ciliary localization of GFP-tagged INPP5E and its redistribution to between the cilia and the plasma membrane (Fansa et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Gotthardt et al (2015) reported that ARL13B serves as a GEF for ARL3, which in turn binds to and stimulates release of PDE6D from C-terminally prenylated proteins, including INPP5E, which are then allowed to enter cilia (Fansa et al, 2016;Ismail et al, 2011). Furthermore, Fansa et al reported that treatment of cells with ARL3 siRNA caused substantial loss of the dominant ciliary localization of GFP-tagged INPP5E and its redistribution to between the cilia and the plasma membrane (Fansa et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…ARL13B has been shown to interact with and participate in the ciliary targeting of another JBTS protein INPP5E (the gene encoding this protein is also known as JBTS1) (Humbert et al, 2012), which is a phosphoinositide 5-phosphatase. Recently, ARL13B has been reported to serve as a guanine nucleotide exchange factor (GEF) for ARL3 (Gotthardt et al, 2015), which interacts with PDE6D (Linari et al, 1999;Van Valkenburgh et al, 2001), another JBTS protein (the gene encoding this protein is also known as JBTS22). PDE6D is known to bind to C-terminally prenylated proteins, including INPP5E, and ARL3 stimulates release of PDE6D from prenylated proteins (Fansa et al, 2016;Ismail et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The structure shows that Arl13B contacts Arl3 via its switch regions, which explains the finding that the GEF activity of Arl13B is dependent on its nucleotide state. Although the structure could not delineate the exact mechanism of how the nucleotide is kicked out, biochemical experiments suggest that an extended helical end (not visible in the structure) could directly reach into and interfere with the nucleotide binding site of Arl3, 48 as demonstrated previously for many other GEFs.…”
Section: Manipulation Of the Affinity Between Carrier And Cargo And Cmentioning
confidence: 82%
“…Such an Arl3-GEF was indeed identified as Arl13B. 48 Arl13B is a GTP-binding protein itself, which in addition to the G domain contains a coiled-coil and a proline-rich domain and localizes exclusively inside the cilium. 49 Surprisingly the G domain and a part of the CC domain are responsible for the GEF activity.…”
Section: Manipulation Of the Affinity Between Carrier And Cargo And Cmentioning
confidence: 95%
“…Indeed both PDE6D and INPP5E are disease genes in Joubert syndrome, a neurodevelopmental ciliopathy clinically defined as the presence of a "molar tooth sign" on axial MRI alongside one or more classic ciliopathy presentations [11,12]. Mutations in INPP5E have been reported in a number of JBTS patients [11,13] throughout the gene; widely in the phosphatase domain, but also in the CAAX domain, required for interaction with PDE6D, and the SH3 domain, required for interaction with Arl13b [13][14][15] suggesting the importance of GSF trafficking in healthy ciliogenesis.…”
Section: Gdi-like Solubilizing Factors (Gsfs)mentioning
confidence: 99%